2022
DOI: 10.1039/d1an02325j
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Doped polydopamine nanoparticles with peroxidase-mimicking activity for the detection of hypoxanthine related to meat freshness

Abstract: Rapid and accurate monitoring of food freshness to provide consumers with high quality meat continues to be of tremendous importance to the food industry. In this report, an efficient Fe-doped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In the high-resolution Fe 2p spectrum (Figure f), the peaks at 710.43, 724.03, 712.04, and 725.64 eV were assigned to Fe­(II) 2p3/2, Fe­(II) 2p1/2, Fe­(III) 2p3/2, and Fe­(III) 2p1/2, respectively, indicating that the valence state of iron in Fe-γ-CD existed in both +2 and +3 valence states. The area distribution ratio of Fe­(II)/Fe­(III) was estimated to be approximately 6:5, suggesting that the dominant form of Fe present in Fe-γ-CD was +2. The C 1s spectrum (Figure g) showed a peak at 288.3 eV, which could be attributed to the CC bond, indicating that γ-CD was a reducing agent converting Fe­(III) into Fe­(II) . Finally, the O 1s spectrum revealed (Figure h) subpeaks corresponding to H–O, C–O, and Fe–O bonds with an observed peak at 529.66 eV confirming successful connection between Fe and γ-CD.…”
Section: Synthesis and Characterization Of The Fe-γ-cdmentioning
confidence: 84%
“…In the high-resolution Fe 2p spectrum (Figure f), the peaks at 710.43, 724.03, 712.04, and 725.64 eV were assigned to Fe­(II) 2p3/2, Fe­(II) 2p1/2, Fe­(III) 2p3/2, and Fe­(III) 2p1/2, respectively, indicating that the valence state of iron in Fe-γ-CD existed in both +2 and +3 valence states. The area distribution ratio of Fe­(II)/Fe­(III) was estimated to be approximately 6:5, suggesting that the dominant form of Fe present in Fe-γ-CD was +2. The C 1s spectrum (Figure g) showed a peak at 288.3 eV, which could be attributed to the CC bond, indicating that γ-CD was a reducing agent converting Fe­(III) into Fe­(II) . Finally, the O 1s spectrum revealed (Figure h) subpeaks corresponding to H–O, C–O, and Fe–O bonds with an observed peak at 529.66 eV confirming successful connection between Fe and γ-CD.…”
Section: Synthesis and Characterization Of The Fe-γ-cdmentioning
confidence: 84%
“…Encouraged by the excellent peroxidase-like activity of bimetallic Fe@CeO 2 above, the Hx-triggered Fe@CeO 2 -based enzymatic cascade catalytic system was next explored. It has been reported that XOD possessed the catalytic activity to convert Hx into H 2 O 2 , 9 which might create an opportunity to combine with Fe@CeO 2 to realize an Hx-triggered enzymatic cascade catalytic system for producing • OH. To prove this speculation, the colorimetric assay based on the oxidation conversion of colorless TMB into dark-blue oxTMB with high absorbance at 652 nm was again performed in HAc−NaAc buffer.…”
Section: Construction Of the Fe@ceo 2 -Based Enzymatic Cascade Cataly...mentioning
confidence: 99%
“…In this case, nonvolatile hypoxanthine (Hx), a product of adenosine triphosphate (ATP) decomposition after a series of reactions during meat spoilage, has become one of the research hotspots to be employed as an indicator of meat spoilage in the meat processing industry. 9,10 Driven by this, vast efforts have been focused on developing efficient assays, such as high-performance liquid chromatography (HPLC), 11 electrochemistry, 12 colorimetry, 13 fluorometry, 14 etc., to detect Hx for judging meat freshness. Although these reported approaches have satisfactory results for detecting Hx to judge meat freshness, they all stay in the single analytical mode and are easily affected by the real meat matrices to yield falsepositive output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 PDA is often used as an immobilization matrix for functional molecules and materials, due to its abundant active functional groups or structural units (amine, catechol, quinone, and indole). 27–29 The CdS quantum dots (CdS QDs) material, an important II–VI semiconductor with a narrow bandgap of ca. 2.4 eV, has the advantages of a wide light absorption range, high carrier separation efficiency, and relatively negative E CB ( ca.…”
Section: Introductionmentioning
confidence: 99%